2016
DOI: 10.3402/qhw.v11.30490
|View full text |Cite
|
Sign up to set email alerts
|

Self and identity in women with symptoms of borderline personality: A qualitative study

Abstract: Identity disturbance has been suggested to be a core feature of borderline personality disorder (BPD). However, there is little known about the identity of individuals with symptoms of BPD from the participant's perspective. This study availed of in-depth lightly structured life story interviews with five female participants. Thematic analysis was utilized to derive three themes of identity: connection, distance between us, and hurt and healing. Results provided support for multiple and flexible conceptualizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…The data also parallels Agnew and colleagues' study that “highlighted the complex and intertwined nature of traumatic experience, personality organization, and self/identity” [( 19 ), p. 8]. Crucially important in defining a self-concept within the current study, were women's experiences from the past, including trauma resulting from physical, psychological or sexual abuse, the quality of early life attachments, transience in housing and schooling, relationships with siblings and parents, experiences at school and access to physical and economic resources.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The data also parallels Agnew and colleagues' study that “highlighted the complex and intertwined nature of traumatic experience, personality organization, and self/identity” [( 19 ), p. 8]. Crucially important in defining a self-concept within the current study, were women's experiences from the past, including trauma resulting from physical, psychological or sexual abuse, the quality of early life attachments, transience in housing and schooling, relationships with siblings and parents, experiences at school and access to physical and economic resources.…”
Section: Discussionsupporting
confidence: 81%
“…Researchers have explored the relationship between psychiatric symptoms and disruptions or incongruence in self-concept ( 19 , 20 ) including models of conceptualizing and mitigating the impact of complex trauma on ones' identity and healing ( 21 ). Wisdom et al ( 5 ) found loss of self to be the most prominent focus of narratives, with the illness “often described as taking away…their previously held identity” (p. 491).…”
Section: Introductionmentioning
confidence: 99%
“…Such a formulation holds as a premise that this process starts from a state of disconnectedness. Reporting from a thematic analysis of interviews with five women diagnosed with BPD, Agnew et al (2016) found three identity themes, which they coin connection, distance between us, and hurt and healing. They describe how these women understood their suffering as having relational origins and relational solutions, and that in recovery, finding ways of connecting constructively to others was important.…”
Section: Discussionmentioning
confidence: 99%
“…Previous qualitative research on BPD patients' subjective experience of recovery has identified connectedness as a relevant dimension in the change process. For example, reporting on a thematic analysis of interviews with five women diagnosed with BPD, Agnew et al (2016) described how the participants understood their suffering as having relational origins and therefore, relational solutions. Consequently, finding ways of connecting constructively with others was regarded as important in recovery.…”
Section: Discussionmentioning
confidence: 99%